2015
DOI: 10.1177/089875641503200102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frequency of Brushing Teeth on Plaque and Calculus Accumulation, and Gingivitis in Dogs

Abstract: The efficacy of brushing the teeth of beagle dogs in a randomized, controlled, blinded study design using a clearly-defined brushing technique was evaluated for 4 brushing frequencies: brushing daily, brushing every other day, brushing weekly and brushing every other week, compared with no brushing in a control group of dogs. All dogs were fed a standard dry kibble diet during the study. Standard plaque, calculus, and gingivitis indices were used to score the teeth. A 'clean tooth' model was used. No gingival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 9 publications
4
43
0
Order By: Relevance
“…Although a previous study stated that oral hygiene practices such as TB and DF were not associated with periodontitis (Merchant et al., ), the recent review showed that infrequent TB was related to having severe periodontal disease (Zimmermann et al., ). Another recent study reported that the mean of dental plaque and calculus scores were reduced by TB (Harvey et al., ). Cochrane review recommended TB twice a day to prevent caries (Marinho, Higgins, Sheiham, & Logan, ), but the recent systematic review stated that the effect of frequency of toothbrushing to dental caries is unclear and the evidence of toothbrushing twice a day was not strong (Kumar, Tadakamadla, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a previous study stated that oral hygiene practices such as TB and DF were not associated with periodontitis (Merchant et al., ), the recent review showed that infrequent TB was related to having severe periodontal disease (Zimmermann et al., ). Another recent study reported that the mean of dental plaque and calculus scores were reduced by TB (Harvey et al., ). Cochrane review recommended TB twice a day to prevent caries (Marinho, Higgins, Sheiham, & Logan, ), but the recent systematic review stated that the effect of frequency of toothbrushing to dental caries is unclear and the evidence of toothbrushing twice a day was not strong (Kumar, Tadakamadla, & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Toothbrushing (TB) has been regarded as fundamental self-care behaviour activity for keeping good oral health. Frequent toothbrushing has been considered an effective factor for reduction in oral plaque (Harvey, Serfilippi, & Barnvos, 2015). The use of dental floss (DF) is a widely used self-care method for inter-dental cleaning (Sambunjak et al, 2011;Warren & Chater, 1996), and inter-dental brushing (IDB) is an effective method for the removal of inter-proximal plaque (Poklepovic et al, 2013;Salzer, Slot, Van der Weijden, & Dorfer, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous work by others that showed ≥⃒60% reduction in mean (±sd) plaque scores when comparing daily brushing with no brushing (3.1 [±0.80] versus 4.9 [±1.14]) or a daily dental chew to no brushing (7.74 [±0.65] versus 11.42 [±1.20]) (Brown & McGenity , Harvey et al . ), it was estimated that a minimum of six to eight dogs per treatment group would be required to be 95% confident of detecting a 25% reduction in plaque accumulation ( i.e . from a mean of 7.74 to 5.81 with sd of 1.0 to 1.2 for what we considered to be a clinically significant difference among the treatment groups with no negative control group) with 80 to 90% power (Statulator beta.…”
Section: Methodsmentioning
confidence: 99%
“…1). Based on previous work by others that showed ≥60% reduction in mean (±sd) plaque scores when comparing daily brushing with no brushing (3.1 [±0.80] versus 4.9 [±1.14]) or a daily dental chew to no brushing (7.74 [±0.65] versus 11.42 [±1.20]) (Brown & McGenity 2005, Harvey et al 2015, it was…”
Section: Recruitment and Enrolmentmentioning
confidence: 99%
See 1 more Smart Citation